OPTIMIZATION OF HARVEST TIME FOR BIOMASS AND PHYCOBILIPROTEIN PRODUCTION OF Spirulina sp. CULTIVATED IN GANYONG (Canna edulis) SHOOT WASTE–BASED LIQUID ORGANIC FERTILIZER - Risa Swandari Wijihastuti; Nita Noriko; Nadhira Saffana; Akifah Lutfiah; Botista Agung Maryanto (Universitas Mataram, 2026)
Spirulina sp. is a microalga with high economic value and strong potential as a source of protein and bioactive pigments for functional food, cosmetic and pharmaceutical applications. This study aimed to evaluate the growth performance, protein and pigment contents, and to determine the optimal harvest time of Spirulina sp. cultured using liquid organic fertilizer (LOF) produced from fermented ganyong shoot waste (Canna edulis). The culture was conducted for 16 days using LOF media at concentrations of 14 and 18 ml/L. The observed parameters included dry biomass weight, specific growth rate, biomass productivity, protein content, chlorophyll-a and phycobiliprotein pigments throughout the cultivation period. The results showed that Spirulina sp. biomass increased by approximately fivefold compared to the initial biomass in both treatments. Specific growth rate, biomass productivity, and protein content did not differ significantly between the two LOF concentrations (p > 0.05), with protein content ranging from 42% to 55% of dry biomass weight. Chlorophyll-a and phycobiliprotein contents varied according to the growth phase of the culture. The highest phycobiliprotein content was obtained in cultures grown with 14 mL/L LOF and harvested on day 8 of cultivation. These findings indicate that liquid organic fertilizer derived from ganyong shoot waste has strong potential as a sustainable alternative nutrient source for biomass and pigment production of Spirulina sp., with the exponential growth phase representing the optimal harvest time.